2019
DOI: 10.18332/tpc/108553
|View full text |Cite|
|
Sign up to set email alerts
|

Is adolescent e-cigarette use associated with smoking in the United Kingdom?: A systematic review with meta-analysis

Abstract: INTRODUCTION Though smoking is a public health problem the use of e-cigarettes has been associated with a reduction in smoking in developed countries. However, public health experts have raised concerns about the association of e-cigarette use with an increase in traditional cigarette smoking in adolescents. Reviewlevel evidence is generally supportive of this concern, but as it is mainly based on studies from the USA we investigated if e-cigarette use is associated with traditional cigarette smoking in adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 36 publications
7
45
0
Order By: Relevance
“…The results of this up-to-date and comprehensive systematic review are in line with two previous meta-analyses, Soneji et al [16] and Aladeokin and Haighton [18], that also found an association between initiation of e-cigarette use and subsequent smoking. However, this systematic review consolidates and extends the evidence base for public health policy because it used nine studies concentrating on adolescents who resided in a wider geographical region, and the analysis also took account of quality and confounding.…”
Section: Comparison With Previous Systematic Reviewssupporting
confidence: 89%
“…The results of this up-to-date and comprehensive systematic review are in line with two previous meta-analyses, Soneji et al [16] and Aladeokin and Haighton [18], that also found an association between initiation of e-cigarette use and subsequent smoking. However, this systematic review consolidates and extends the evidence base for public health policy because it used nine studies concentrating on adolescents who resided in a wider geographical region, and the analysis also took account of quality and confounding.…”
Section: Comparison With Previous Systematic Reviewssupporting
confidence: 89%
“…This review builds on and has findings consistent with earlier systematic reviews and metaanalyses in the peer-reviewed and grey literature [11,16,38,39,58,59] For those who use nicotine-containing e-cigarettes, a resulting addiction to nicotine may leave users at risk of seeking other forms of inhalable nicotine, such as combustible cigarettes [60,61]. Additionally, as e-cigarettes can mimic behavioural (e.g.…”
Section: Discussionsupporting
confidence: 53%
“…Aladeokin & Haighton (2019) aimed to systematically review the evidence on e-cigarette use and initiation of cigarette smoking in adolescents (aged 10-19 years old) in the UK and included eight studies. [39] Their meta-analysis showed e-cigarette users were much more likely than non-users to go on to smoke combustible cigarettes, even after adjusting for covariates (see Table 1); the substantial heterogeneity in the summary estimate should be noted.…”
Section: Umbrella Reviewmentioning
confidence: 98%
“…Evidence shows that those who use e-cigarettes earlier are more prone to smoke regular cigarettes in the future 2 . A recent study revealed that adolescents who use e-cigarettes are up to six times more likely to smoke traditional cigarettes 3 . E-cigarettes are considered a tobacco product because they contain nicotine, a highly addictive substance.…”
Section: Dear Editormentioning
confidence: 99%